Stochastic Dominance Analysis for the Poverty in Tabalong Regency 2013 and 2017 - Murjani, Ahmadi (Jurnal Bina Praja, 2018)
Although its issue could be addressed from of various perspectives over the years, poverty is the object of the government’s policy programs to be alleviated since the Indonesian independence. With the advancement of technology and science in the recent decades, the availability and the completeness of poverty data in Indonesia getting better. In fact, the policy-makers can assess the effectivity of their public-oriented programs easier by effectively utilizing the complete and up-to-date poverty data. However, in various approaches to poverty measurement, the Indonesian poverty data should be accompanied by another approach. This paper aims to evaluate the change of welfare of particular region over a period of several years by using the stochastic dominance method. This method also incorporates the price level impact into its poverty assessment through the extrapolated CPIs. To conduct the measurement, the National Socioeconomic Survey of Tabalong regency data, as well as the Tanjung city’s inflation in the period from 2013 to 2017, are employed. The results indicate that the welfare in 2017 is better than in 2013 since the distribution in 2017 stochastically dominates the distribution in 2013 at the first and second order at any possible level of poverty lines. Therefore, this result could also be the additional input for the poverty alleviation’s evaluation in order to provide a solid conclusion about the welfare changes.